La contratación pública y la participación de artesanos en el Gobierno Autónomo Descentralizado Municipal del cantón Tosagua - Alcívar Chávez, María Lourdes (2025)
The present research aimed to analyze public procurement and the participation of artisans in the Municipal Decentralized Autonomous Government of Tosagua, with the objective of establishing improvement actions. To achieve this, a methodology was employed that integrated interviews and surveys based on the Likert scale model, along with inductive, deductive, and analytical-synthetic methods, in addition to bibliographic and field research. Among the main findings, the diagnosis of artisan participation in public procurement at the GAD of Tosagua revealed several deficiencies, such as many artisans being unaware of what public procurement entails, others not knowing how to participate in such processes, and a high degree of unfamiliarity with inclusive fairs, as a large portion of respondents had not participated in these types of events. Based on this data, a proposed action plan was established, including activities such as workshops, training sessions, and awareness and outreach campaigns, all aimed at addressing and reducing the identified problems.